“Golden” cascade cyclization to Benzo[c]-Phenanthridines - Hendrich, Christoph; Senn, Sebastian; Haas, Lea; Hoffmann, Marvin; Zschieschang, Ute; Greiner, Luca C.; Rominger, Frank; Rudolph, Matthias; Klauk, Hagen; Dreuw, Andreas; Hashmi, A. Stephen K. (Chemistry - a European journal, 2021)
Herein, we describe a gold-catalyzed cascade cyclization of Boc-protected benzylamines bearing two tethered alkyne moieties in a domino reaction initiated by a 6-endo-dig cyclization. The reaction was screened intensively, and the scope was explored, resulting in nine new Boc-protected dihydrobenzo[c]phenanthridines with yields of up to 98 %; even a π-extension and two bidirectional approaches were successful. Furthermore, thermal cleavage of the Boc group and subsequent oxidation gave substituted benzo[c]phenanthridines in up to quantitative yields. Two bidirectional approaches under the optimized conditions were successful, and the resulting π-extended molecules were tested as organic semiconductors in organic thin-film transistors.
Gesehen am 28.03.2023